PENGEMBANGAN PEMBELAJARAN SEJARAH DENGAN SCIENTIFIC APPROACH MELALUI OUTDOOR STUDY DI KELAS XI IIS 4 SMA NEGERI AJIBARANG - Apriliana, Diah (Indonesian Journal of History Education, 2015)
This research aims to develop a history lesson in class XI social science secondary schools overcome Ajibarang. This study uses a design research and development (Research and Development). This study was conducted in Class XI social science secondary schools Ajibarang 2014/2015. The approach used in this study is the R and D quantitative approach with experimental design pattern Design.Pengambilan Pre Test Post Test samples were obtained 2 classes of class X social science as an experimental class of carrying out the pre-test and post test with classroom learning outside the classroom XI social science as the control class in the form of implementation of the pre-test and post-test with conventional learning. Before doing penelitien first design learning development lecturer.Hasil validated by the validation of the learning progression meet the criteria of decent so it can be tested. Â